2016
DOI: 10.1111/dom.12821
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events and all‐cause mortality associated with sulphonylureas compared with other antihyperglycaemic drugs: A Bayesian meta‐analysis of survival data

Abstract: Aim To conduct a systematic review and meta‐analysis to determine the risk of cardiovascular events and all‐cause mortality associated with sulphonylureas (SUs) vs other glucose lowering drugs in patients with T2DM (T2DM). Materials and methods A systematic review of Medline, Embase, Cochrane and http://clinicaltrials.gov was conducted for studies comparing SUs with placebo or other antihyperglycaemic drugs in patients with T2DM. A cloglog model was used in the Bayesian framework to obtain comparative hazard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(55 citation statements)
references
References 31 publications
0
47
0
6
Order By: Relevance
“…1,5 In addition, there is an ongoing controversy regarding their long-term cardiovascular safety, based on early data from the University Group Diabetes Program in the 1960s 8 and multiple observational and smaller studies indicating conflicting results. 9,10 Linagliptin is a selective, once-daily, DPP-4 inhibitor approved for glycemic management of type 2 diabetes, with low risk of hypoglycemia and weight neutrality. 11 To date, no headto-head trial has compared the long-term effect of these agents on cardiovascular morbidity and mortality or glucoselowering efficacy in patients with type 2 diabetes.…”
mentioning
confidence: 99%
“…1,5 In addition, there is an ongoing controversy regarding their long-term cardiovascular safety, based on early data from the University Group Diabetes Program in the 1960s 8 and multiple observational and smaller studies indicating conflicting results. 9,10 Linagliptin is a selective, once-daily, DPP-4 inhibitor approved for glycemic management of type 2 diabetes, with low risk of hypoglycemia and weight neutrality. 11 To date, no headto-head trial has compared the long-term effect of these agents on cardiovascular morbidity and mortality or glucoselowering efficacy in patients with type 2 diabetes.…”
mentioning
confidence: 99%
“…In an analysis of 115 randomized trials in people with type 2 diabetes, sulphonylurea therapy increased mortality by 22% compared with placebo or other glucose‐lowering therapies, but the overall incidence of MACE was unaffected . Two further recent analyses have concluded that sulphonylurea therapy increases the risk of CV deaths compared with other oral glucose‐lowering therapies: CV deaths were increased by 27% in an analysis of 33 studies, and by 46% in an analysis of 82 randomized controlled trials; however, another recent analysis of 47 randomized trials in people with type 2 diabetes found no increase in CV mortality with use of a sulphonylurea, including add‐on to metformin . Sulphonylurea therapy in overweight patients in the UKPDS was less beneficial than metformin, and an evaluation of 14 randomized trials comparing the two agents suggested that sulphonylurea therapy carries a 47% greater risk of CV mortality than metformin, although this was not quite statistically significant .…”
Section: Antidiabetic Drugs and CV Effectsmentioning
confidence: 99%
“…4,29 In an analysis of 115 randomized trials in people with type 2 diabetes, sulphonylurea therapy increased mortality by 22% compared with placebo or other glucose-lowering therapies, but the overall incidence of MACE was unaffected. 30 Two further recent analyses have concluded that sulphonylurea therapy increases the risk of CV deaths compared with other oral glucose-lowering therapies: CV deaths were increased by 27% in an analysis of 33 studies, and by 46% in an analysis of 82 randomized controlled trials 31,32 ;…”
Section: Sulphonylureas and Meglitinidesmentioning
confidence: 99%
“…Since the approval of exenatide, the first glucagon‐like peptide‐1 (GLP‐1) agonist, and now the sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors, we have the tools necessary to achieve good glycaemic control with concomitant weight loss . With weight loss, we can hope to decrease cardiovascular risk and diabetic comorbidities . To date, there are limited data on the concomitant use of these classes of drugs.…”
Section: Stepwise Treatment In 46 Of 79 Patientsmentioning
confidence: 99%